Analysis of Second Order Person-Environment Fit on Innovative Work Behavior and Individual Performance - Mohamad Yanuar Mufti; Emiliana Sri Pudjiarti; Susetyo Darmanto (LifeSciFi, 2019)
The most important aspect of generating a competitive advantage is to advance the quality of human resources controlled by the company. One way to advance the quality of human resources is to enhance the quality of work-life as well as creating Innovative Work Behavior. This study aims to ascertain whether there is a positive and significant correlation between the second-order (2nd order) person-environment fit, quality of work-life on Innovative Work Behavior, and individual performance. The study was conducted on employees of PDAM Tirto Panguripan of Kendal District with a total of 180 respondents. Samples were taken using the technique of Stratified Random Sampling. The data collection method is carried out using questionnaires and interviews. Data analysis was performed with SEM through AMOS version 22 software. The outcomes of the analysis showed that the P-E fit and quality of work-life are significant with employee performance and Innovative Work Behavior has proven to be a mediation.